PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN PEMBERIAN PUPUK NPK DAN KOMPOS SEKAM PADI PADA MEDIA INCEPTISOL - Syahri Ramadhan; Besri Nasrul (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
Oil palm is a plantation crop that plays a strategic role in the Indonesian economy because this commodity has bright prospects as a source of foreign exchange. The experiment aims to know the effect of interaction giving NPK fertilizer and rice husk compost and get the best combination dose for the growth of oil palm seedlings in the main nursery. The research was conducted experimentally using a completely randomized design factorial with two factors, such as factor of NPK fertilizer (P) which consists of three extents, that are NPK 0 g/plant, NPK 12,5 g/plant, and NPK 25 g/plant. The second factor is rice husk compost (K) which consists of 4 extents that are rice husk compost 0 g/plant, rice husk compost 150 g/plant, rice husk compost 250 g/plant and rice husk compost 350 g/plant. The parameters observed included an increase in seedling height, an increase in stem diameter, an increase in leaf number, root volume, seed dry weight, and root crown ratio. The results showed that the application of NPK fertilizer and rice husk compost was able to increase the growth of oil palm seedlings in the main nursery. The application of NPK fertilizer and rice husk compost significantly increased the increase in plant height, wee diameter, leaf number, root volume, plant dry weight, and seedling root crown ratio. The combination of NPK fertilizer application according to the recommended dose (25 g/plants) and 250 g of rice husk compost per plant gave the best results for the growth of oil palm seedlings in the main nursery